Integrative analysis revealed the role of glucagon-like peptide-2 in improving experimental colitis in mice by inhibiting inflammatory pathways, regulating glucose metabolism, and modulating gut microbiota - Li, Dongyue; Gao, Yanhong; Cui, Lanrong; Li, Yang; Ling, Hao; Tan, Xin; Xu, Hongyu (Frontiers in Microbiology, 2023)
Ulcerative colitis (UC) is an inflammatory bowel disease characterized by recurrent and remitting inflammation of the mucosa of the colon and rectum, the incidence of which is on the rise. Glucagon-like peptide-2 (GLP-2) is a newly discovered neurotrophic factor, but its efficacy and mechanism of action in UC remain unclear. In this study, we investigated the protective effects and potential targets of GLP-2 on DSS-induced UC in mice through integrative analysis. The effects of GLP-2 on UC were assessed by calculating the disease activity index, colonic mucosal damage index and pathological histological scores. ELISA and immunohistochemistry were used to detect the expression of GLP-2, NF-κB, IL-6 and STAT3. The 16SrRNA gene was used to detect changes in gut microbiota in mouse colonic tissues, and OGTT blood glucose levels were used to analyze the differences in flora. The results showed that GLP-2 could reduce the inflammation of UC mice, which may be achieved by inhibiting the potential targets of NF-κB, and JAK/STAT3 inflammatory pathways, regulating sugar metabolism, increasing dominant species, and improving microbial diversity. This study provides new insight into the potential of GLP-2 for achieving more ideal UC treatment goals in the future.